2017
DOI: 10.7554/elife.21283
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the host-pathogen interaction in human tuberculosis using a bioengineered 3-dimensional model

Abstract: Cell biology differs between traditional cell culture and 3-dimensional (3-D) systems, and is modulated by the extracellular matrix. Experimentation in 3-D presents challenges, especially with virulent pathogens. Mycobacterium tuberculosis (Mtb) kills more humans than any other infection and is characterised by a spatially organised immune response and extracellular matrix remodelling. We developed a 3-D system incorporating virulent mycobacteria, primary human blood mononuclear cells and collagen–alginate mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 73 publications
3
65
0
Order By: Relevance
“…They then demonstrated that proteolytic collagen destruction of the lung ECM is the initial pathological event that reduces the survival of Mycobacterium tuberculosis ‐infected cells, resulting in caseous necrosis and cavitation, and so diverting the immune response in favour of the pathogen. Conversely, intact collagen fibrils increase survival of infected cells . In line with this, Parasa et al .…”
Section: The Ecm: An Integral Part Of the Innate Immune Response To Imentioning
confidence: 62%
“…They then demonstrated that proteolytic collagen destruction of the lung ECM is the initial pathological event that reduces the survival of Mycobacterium tuberculosis ‐infected cells, resulting in caseous necrosis and cavitation, and so diverting the immune response in favour of the pathogen. Conversely, intact collagen fibrils increase survival of infected cells . In line with this, Parasa et al .…”
Section: The Ecm: An Integral Part Of the Innate Immune Response To Imentioning
confidence: 62%
“…To validate the successful establishment of a microscale in vitro granuloma model within our platform, we used three separate previously reported readouts: 1) aggregate formation, 2) encapsulation of the mycobacterium within host immune cells, and 3) soluble factor analysis. (Birkness et al 2007; Kapoor et al 2013; Crouser et al 2017; Tezera et al 2017) After initiating infection by mixing MDMs and BCG into the ECM (collagen I) and seeding it into the wells, we consistently observed aggregate formation in the granuloma layer containing BCG when wells were fixed and imaged on Day 4 post infection (p.i.) (Figure 2).…”
Section: Resultsmentioning
confidence: 87%
“…(Peyron et al 2008) However, many of these in vitro models consist of granulomas grown inside of well plates(Peyron et al 2008; Birkness et al 2007; Kapoor et al 2013; Puissegur et al 2004; Crouser et al 2017), limiting the ability of the researchers to easily manipulate the microenvironment of the granulomas and increase the complexity of their granuloma models through multiculture and introduction of key components of the microenvironment on demand. Recently, more complex, biomimetic models have been developed that have successfully recapitulated important biological phenomena(Venkata Ramanarao Parasa et al 2014; Venkata R. Parasa et al 2017) and examined novel therapeutic approaches to combat TB infection (Tezera et al 2017; Bielecka et al 2017), while simultaneously demonstrating innovative and tractable platforms. However, these models face limitations in studies where users wish to subject granulomas to various microenvironmental cues over time, or in enabling the addition of tissue components after the model is established.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, a number of factors may have to be considered in ensuring clinical relevance (BOX 2). In this context, it is worth noting the parallel development and application to Mtb infection studies of increasingly sophisticated systems for three-dimensional cell culture (135,136) since these might offer a useful intermediate in bridging the in vitro / in vivo divide.…”
Section: Introductionmentioning
confidence: 99%